A Qualitative Investigation Into Faith and LGBTQ Identities in a Nonclinical Sample of Readers of the Dear Abby Column: The Dear Abby Project. Issue 12 (9th December 2021) - Ghazzawi, Alhasan; Casoy, Flávio; Libby, Naomi; McIntosh, Chris; Barber, Mary; Adelson, Stewart; Ahola, Joanne; Ashley, Kenneth; Chavez, Alexis M.; Erickson-Schroth, Laura; Fadus, Matthew; Goldenberg, David; et al.
Abstract: To better understand the relationship between faith and LGBTQ+ identity, we conducted a qualitative analysis of 86 respondents to a general question posed through the Dear Abby column. Responses were anonymized and analyzed using a grounded theory approach. Analysis revealed six themes, reflecting a diversity of lived experience from community rejection to acceptance, and self-rejection to feelings of acceptance by God. Despite frequent media portrayals of conflict between faith and LGBTQ+ identity, the reality is more complex, and faith and LGBTQ+ identity development can be complementary.